2016
DOI: 10.1016/j.jsxm.2016.11.316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BKCa Channel Opener LDD175 on Erectile Function in an In Vivo Diabetic Rat Model

Abstract: The results showed that the BKCa channel opener LDD175 improved erectile function in an in vivo diabetic rat model. Furthermore, combination therapy of LDD175 and sildenafil had an additive effect on the improvement of erectile function in diabetic rats. LDD175 could be a new candidate for the treatment of erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…[29,30]. The SHR-S1.5 group presented an improved erectile function, corroborating with reports in the literature [31][32][33]. Interestingly, no differences were observed in terms of the erectile function of the SHR-C100…”
Section: Discussionsupporting
confidence: 89%
“…[29,30]. The SHR-S1.5 group presented an improved erectile function, corroborating with reports in the literature [31][32][33]. Interestingly, no differences were observed in terms of the erectile function of the SHR-C100…”
Section: Discussionsupporting
confidence: 89%
“…The results obtained by Sung and colleagues showed that another activator of these channels, LDD175, improved erectile function in a diabetic rat model. Furthermore, they showed that LDD175 treatment combined with sildenafil had an additive effect on improving the erectile function of diabetic rats (Nilius and Owsianik, 2011;Sung et al, 2017). These findings suggest that BK Ca channels are possible targets for the treatment of ED.…”
Section: Ion Channels and Erectile Dysfunctionmentioning
confidence: 95%
“…In vivo cavernous nerve stimulation was performed to investigate erectile function. The detailed methodology for measuring the erectile response to cavernous nerve stimulation has been described in previous studies [15]. The electrical field stimulation (EFS) parameters were as follows: 1, 2.5, and 5 V, 5 ms, 2 Hz, and a duration of 60 s using an electric stimulator (model PG 721A; Austin Electronic Specialties, Inc., Palo Alto, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The electrical field stimulation (EFS) parameters were as follows: 1, 2.5, and 5 V, 5 ms, 2 Hz, and a duration of 60 s using an electric stimulator (model PG 721A; Austin Electronic Specialties, Inc., Palo Alto, CA, USA). Sub-maximal EFS was introduced with 1 and 2.5 V as previously described [15]. By subdividing the power of stimulation, the subtle effects of erection could be compared among the groups.…”
Section: Methodsmentioning
confidence: 99%